The Phenomenon of Teenage Abortion. - Espedilla, Naomi A.; Lanugan, Ruthsen B. (Naomi A. Espedilla, 2011)
The study basically aims to analyze and understand the phenomenon of teenage abortion. It mainly sought to discover factors that influence teens in doing abortion as well as the major causes and reasons for their action. Moreover the researchers dwell on the methods used and the possible effects of abortion such as number of physical, psychological, emotional, sexual and social problems. Furthermore, the process of healing and recovery of teens is also the objective of the study.